Being in the zone: physiological markers of togetherness in joint improvisation - Noy, Lior; Levit-Binun, Nava; Golland, Yulia (Frontiers in Human Neuroscience, 2015)
Performers improvising together describe special moments of ‘being in the zone’ – periods of high performance, synchrony and enhanced sense of togetherness. Existing evidence suggests ¬a possible route for attaining togetherness - interpersonal synchrony, the fine-grained sensory-motor coordination that promotes social connectedness. Here we investigated the physiological characteristics of togetherness using a practice from theater and dance, the mirror game. Pairs of expert improvisers jointly improvised synchronized linear motion, while their motion tracks and cardiovascular activity were continuously monitored. Players also provided dynamic ratings of togetherness while watching video recordings of their games. We identified periods of togetherness using kinematic and subjective markers and assessed their physiological characteristics. The kinematic and the subjective measures of togetherness showed some agreement, with more extensive game-periods being marked by the subjective than the kinematic one. Game rounds with high rates of togetherness were characterized by increased players’ cardiovascular activity, increased correlation of players’ heart rates, and increased motion intensity. By comparing motion segments with similar motion intensity, we showed that moments of togetherness in the mirror game were marked by increased players’ heart rates, regardless of motion intensity. This pattern was robust for the subjectively defined periods of togetherness, while showing a marginal effect for the kinematically defined togetherness. Building upon similar findings in flow research we suggest that the observed increase of players’ heart rates during togetherness periods in the mirror game might indicate the enhanced engagement and enjoyment reported by performers going into ‘the zone’. The suggested approach, combining temporal measurements of kinematic, physiological and subjective responses, demonstrates how the dynamics of spontaneously emerging dyadic states